Monetary union in crisis : - Moss, Bernard H. (Palgrave Macmillan, 2005)
Moss offers a radically new interpretation of the European Community and Monetary Union as a neo-liberal project. The book places EC development in the context of the post-war long wave, labor mobilization and political class conflict, stressing its role as a Hayekian federation or dike to dampen growth and defeat inflationary working-class demands. The assessment is sustained by a study of EC origins, constitution and policies, econometric evidence, a critique of existing literature and member-state case studies.